2022
DOI: 10.1016/j.cgh.2021.05.056
|View full text |Cite
|
Sign up to set email alerts
|

A Polygenic Risk Score to Refine Risk Stratification and Prediction for Severe Liver Disease by Clinical Fibrosis Scores

Abstract: BACKGROUND & AIMS:A polygenic risk score based on well-known genetic variants in PNPLA3, TM6SF2, MBOAT7, and GCKR predicts hepatic fat content (polygenic risk score-hepatic fat content [PRS-HFC]). Here, we hypothesized that the addition of PRS-HFC to clinical fibrosis scores may improve risk stratification and prediction of severe liver disease (SLD). METHODS:We used data from 266,687 individuals in the UK Biobank, evaluating the incidence of cirrhosis, decompensated liver disease, hepatocellular carcinoma, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 28 publications
(39 reference statements)
4
58
0
Order By: Relevance
“…These notions are corroborated by the slight but consistent outperforming of NFS by the much simpler FIB-4 ( 45 , 50 ). Recent data also suggest that, at the general population level, the ability of NFS to predict incident severe liver disease is inferior to that of FIB-4 among the obese ( 51 ). In addition to age, FIB-4 only includes the aspartate-to-alanine aminotransferase ratio as well as platelets, which are among the best indicators of advanced fibrosis and cirrhosis in routine laboratory tests ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…These notions are corroborated by the slight but consistent outperforming of NFS by the much simpler FIB-4 ( 45 , 50 ). Recent data also suggest that, at the general population level, the ability of NFS to predict incident severe liver disease is inferior to that of FIB-4 among the obese ( 51 ). In addition to age, FIB-4 only includes the aspartate-to-alanine aminotransferase ratio as well as platelets, which are among the best indicators of advanced fibrosis and cirrhosis in routine laboratory tests ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The loci comprising the current risk score are also implicated in the risk for developing cirrhosis of diverse aetiologies. Using similar polygenic risk scores (PRS) in non-alcoholic fatty liver disease (NAFLD) revealed that combining genetic and clinical features refines the predictive utility of the algorithm for identifying those at higher risk of severe liver disease [32][33][34] . Given the many shared genetic and metabolic risks between alcohol-related liver disease and NAFLD, the predictive algorithm defined here may have a wider scope across these diseases for risk stratification of those at higher risk of cirrhosis.…”
Section: Scope Of Risk-scorementioning
confidence: 99%
“…Moreover, hepatitis virus can inhibit bone marrow megakaryocytes, which impairs platelet production, thereby reducing platelet count and their ability to aggregate, and increasing mean platelet volume and width. 42,43 Liver damage is associated with increases in the serum activities of AST and ALT, and these are commonly used as markers of hepatocyte injury. 44,45 These parameters are also used as a means of diagnosing NAFLD early, and the identification of a high-normal serum ALT activity is of great significance for the early prevention of NAFLD.…”
Section: Discussionmentioning
confidence: 99%